2015
DOI: 10.1371/journal.pone.0139527
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Prevalence and Cardiovascular Associations of Diabetic Retinopathy and Maculopathy: Results from the Gutenberg Health Study

Abstract: There are errors in the first sentence of the "Conclusions" subsection of the Abstract. The correct sentence is: Our calculations suggest that approximately 142 000 persons aged between 35 and 74 years have vision threatening diabetic retinal disease in Germany.There are errors in the fourth sentence of the "Prevalence of diabetic retinopathy" subsection of the Discussion. The correct sentence is: The GHS data therefore enables us to state that approximately 142 300 persons in Germany aged between 35 and 74 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
1
5
0
2
Order By: Relevance
“…The duration of diabetes in the DR group was longer than that in the NDR group, and the prevalence of DR was 1.324 times higher in diabetic patients with a disease duration of more than 15 years compared to patients with a disease duration of less than 5 years. This is consistent with the results reported by Dutra et al (prevalence of DR was 1.07 times higher in patients with a disease duration of diabetes more than 15 years compared to patients with (19,20). These findings are related to ocular fundus lesions caused by poor glycemic control.…”
Section: Discussionsupporting
confidence: 93%
“…The duration of diabetes in the DR group was longer than that in the NDR group, and the prevalence of DR was 1.324 times higher in diabetic patients with a disease duration of more than 15 years compared to patients with a disease duration of less than 5 years. This is consistent with the results reported by Dutra et al (prevalence of DR was 1.07 times higher in patients with a disease duration of diabetes more than 15 years compared to patients with (19,20). These findings are related to ocular fundus lesions caused by poor glycemic control.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that obesity, medications, and oxygen therapy are also contributing factors to DR ( Thomas et al, 2012 ; Mcmonnies, 2015 ; Raum et al, 2015 ; Li et al, 2022 ). Raum et al (2015) prospectively identified obesity (BMI ≥ 30) as a risk factor for eyesight loss in DR.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, there is high significant increase in HbA1c between the diseased groups as compared with control. This result agrees with a Chinese study done by Wat et al, [15] who demonstrated an association between higher levels of HbA1C and increased incidence and progression of DR. Another study done by Raum et al, [16] showed that elevated levels of HbA1C were associated with increased risk of DR.…”
Section: Resultsmentioning
confidence: 95%